"TAARgeting Addiction"—The Alamo Bears Witness to Another Revolution: An Overview of the Plenary Symposium of the 2015 Behavior, Biology and Chemistry Conference. (1st February 2016) - Grandy, David K.; Miller, Gregory M.; Li, Jun-Xu
Highlights: Recent progress on trace amine-associated receptor 1 (TAAR1) was described. Historical perspective of TAAR1 and its interaction with dopaminergic system was reviewed. Both in vitro and in vivo evidence support the critical role of TAAR1 in drug addiction. Abstract: Background: In keeping with the free-thinking tradition San Antonians are known for, the Scientific Program Committee of the Behavior, Biology and Chemistry: Translational Research in Addiction Conference chose trace amine-associated receptor 1 (TAAR1) as the focus of the plenary symposium for its 7th annual meeting held at the University of Texas Health Science Center at San Antonio on March 14 and 15, 2015. The timing of the meeting's plenary session on TAAR1 coincided with the Ides of March, an apt concurrence given the long association of this date with the overthrow of the status quo . And whether aware of the coincidence or not, those in attendance witnessed the plunging of the metaphorical dagger into the heart of the dopamine (DA) transporter (DAT)-centric view of psychostimulant action. Methods: The symposium's four plenary presentations focused on the molecular and cellular biology, genetics, medicinal chemistry and behavioral pharmacology of the TAAR1 system and the experimental use of newly developed selective TAAR1 ligands. Results: The consensus was that TAAR1 is a DA and methamphetamine receptor, interacts with DAT and DA D2 receptors, and is essential in modulating addiction-related effects of psychostimulants. Conclusions: Collectively the findings presented during the symposium constitute a significant challenge to the current view that psychostimulants such as methamphetamine and amphetamine solely target DAT to interfere with normal DA signaling and provide a novel conceptual framework from which a more complete understanding of the molecular mechanisms underlying the actions of DA and METH is likely to emerge.